(3JjSjQ GdJSjjQ GdeGdj ddeDSSIs - (3HheOjf(B, (3jhSas ((3GdLRGFQs (3OGQ HdbjSs, 2016)
(3WQM dfG gPG GdcJGH GdejRGfjI GdeGdjI habG ddeYGjjQ GdOhdjI ddeMGSHI,hJMdjdgG HGSJNOGe eDTQGJ GdJhGRf GdeGdj,eY bjGS GdCOGA HGSJNOGe MSGHGJ GdfJGFL h GdfSH GdeGdjI eY JjSjQ GdNRjfI HGSJYeGd LOhd GdJOabGJ, HGdGVGaI Edi LOhd GdJehjd hGdGSJKeGQ, hJjSjQ GMJjGLGJ QCS GdeGd GdYGed GdeYjGQj, hCNjQG GdJbjje GdeGdj ddeTGQjY GdGSJKeGQjI(B. s
Keywords: (3GdEOGQI GdeGdjIs; (3GdeGdjI GdYGeIs